Cyp17a2 is involved in testicular development and fertility in male Nile tilapia, Oreochromis niloticus - Yang, Lanying; Wu, You; Su, Yun; Zhang, Xuefeng; Chakraborty, Tapas; Wang, Deshou; Zhou, Linyan (Frontiers in Endocrinology, 2022)
Steroid hormones play an essential role in many reproductive processes of vertebrates. Previous studies revealed that teleost-specific Cyp17a2 (cytochrome P450 family 17 subfamily a 2) might be required for the production of cortisol in the head-kidney and 17α,20β-dihydroxy-4-pregnen-3-one (DHP) in ovary during oocyte maturation. However, the role of Cyp17a2 in male reproduction remains to be largely unknown. To further explore its essentiality in male steroidogenesis, the homozygous mutation line of cyp17a2 gene was constructed and the effects on spermatogenesis and male fertility were investigated in Nile tilapia (Oreochromis niloticus). EIA and LC-MS/MS measurements demonstrated that cyp17a2 gene mutation resulted in the significant decline of serum 17α-OHP, DHP and cortisol levels, but not androgens and estrogens in fish. On the contrary, a significant increase in intermediate products of cortisol and DHP were found in cyp17a2-/- male fish. The deficiency of cyp17a2 led to the arrest of meiotic initiation in male fish revealing the reduction of the expression of germ cell-related genes (vasa, piwil, oct4) and meiosis-related genes (spo11 and sycp3) by 90 dah. Afterwards, spermatogenesis was gradually recovered with the development of testis in cyp17a2-/- males, but it showed lower sperm motility and reduced fertility compared to cyp17a2+/+ fish. Deletion of cyp17a2 led to the abnormal upregulation of steroidogenic enzymes in the head-kidney. Taken together, our findings proved that, for the first time, Cyp17a2 is indispensable for cortisol and DHP production and cyp17a2 deficiency associated curtailed meiotic initiation and subfertility suggesting the essentiality of DHP and cortisol in the male fertility of fish.